Pengelolaan Mangrove di Madura: Analisis Awal Land Use dan Land Tenure - Amir Mahmud (NUMADURA: Journal of Islamic Studies, Social, and Humanities, 2023)
Mangroves almost grow evenly across the coastal areas of Madura Island and its groups of islands, although the conditions vary (bad and good) based on the land cover of each location. From an ecosystem services perspective, mangroves have an important function for humans and nature in terms of provisioning, regulating and maintaining, and culture. The aim of this study is to describe the forms of land use for mangrove in district spatial planning and the practices of land tenure for mangrove in four districts on Madura Island. By relying on literature review methods and being complemented by observations and interviews, the data was elucidated analytical descriptive. The result of the study shows that the use of mangrove ecosystems tends to be emphasized in regulating and maintaining services (disaster prevention) and less in cultural services (tourism); however, the restraining implementation of space use did not work adequately to control the land conversion threat. In terms of land tenure, mangrove-covered land was controlled by parties depending on location, namely individuals, communities, companies, and government agencies that manage natural resources. Mangroves have great opportunities based on ecosystem services whose development needs to be increased while preventing and stopping threats to the existence and sustainability of mangroves.